Oracle Certified Professional Java SE 7 Programmer Exams 1Z0-804 and 1Z0-805 A Comprehensive OCPJP 7 Certification Guide - Ganesh, S G.; Sharma, Tushar; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Oracle Certified Professional Java SE 7 Programmer Exams 1Z0-804 and 1Z0-805 is a concise, comprehensive, step-by-step, and one-stop guide for the Oracle Certified Professional Java SE 7 Programmer Exam. The first two chapters set the stage for exam preparation and let the reader get started quickly. The first chapter answers frequently asked questions about the OCPJP exam. This book assumes that the reader is already familiar with Java fundamentals which is in line with the prerequisite of having a OCAJP certification. The book sports considerable supportive material to help the reader in effective exam preparation in the form of appendices: 2 mock tests to give the reader a sense of a real-exam. An instant refresher summarizing the most important concepts (with tips on answering questions) to revise just before the exam. This book will be a delectable read for any OCPJP aspirant because of its simple language, example driven approach, and easy-to-read style. Further, given its 100% focus on the exam and helpful supportive material, this book is clearly an attractive buy to OCPJP aspirants worldwide.
Keywords: Computer science; Computer Science; Computer Science, general